2011
DOI: 10.3109/10253890.2011.578266
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress correlates with disturbed sleep: A link connecting stress and cardiovascular disease

Abstract: The association between stress and cardiovascular disease (CVD) risk is becoming established. A mechanistic link clarifying the intermediate steps between the experience of stress and the development of CVD would support this association. We sought to examine the role of perceived stress as a factor associated with disturbed sleep with the goal of providing an explanation for the stress-CVD connection. We performed a cross-sectional analysis of data recorded by subjects at entry to our CVD prevention program. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
88
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 34 publications
9
88
2
Order By: Relevance
“…Further, consistent with findings from adult studies, greater perceived stress was associated with both poorer sleep quality and shorter sleep duration (Kashani et al, 2012;Lund et al, 2010). Interestingly, perceived stress accounted for substantially more variance in sleep quality than sleep duration, suggesting that the quality, not the quantity of youth's sleep is more susceptible to the adverse effects of perceived stress.…”
Section: Pre-conditions Of Mediationsupporting
confidence: 78%
See 1 more Smart Citation
“…Further, consistent with findings from adult studies, greater perceived stress was associated with both poorer sleep quality and shorter sleep duration (Kashani et al, 2012;Lund et al, 2010). Interestingly, perceived stress accounted for substantially more variance in sleep quality than sleep duration, suggesting that the quality, not the quantity of youth's sleep is more susceptible to the adverse effects of perceived stress.…”
Section: Pre-conditions Of Mediationsupporting
confidence: 78%
“…Experimental findings based on animal studies show that chronic stress exposure results in adverse sleep architecture changes, including decreased slow-wave sleep, decreased REM sleep latency, and increased REM sleep (Adrien et al, 1991;Cheeta et al, 1997). In adults, greater report of perceived stress over the past month was associated with poorer sleep quality and shorter sleep duration (Kashani et al, 2012;Lund et al, 2010). In youth, cross-sectional findings show that greater exposure to stressful life events over the past year adversely affects both subjectively-reported and objectively-measured sleep.…”
mentioning
confidence: 99%
“…Job stress is associated with fatigue. For example, Kashani et al [2012] found that individuals experiencing high stress had more daytime sleepiness, greater fatigue, poorer sleep quality, and shorter sleep duration than those who experienced low stress. Fatigue is associated with depression [Slaven et al 2011] and can also impair job performance [Dawson and Reid 1997].…”
Section: Discussionmentioning
confidence: 99%
“…Shortened and disturbed sleep has been associ ated with increased risk for cardiovascular disease (Dimsdale et al, 2000;Kashani, Eliasson, & Varnalis, 2012). Furthermore, increased levels of perceived stress are correlated with shortened total sleep time, suboptimal sleep scores on a variety of sleep quality questionnaires, increased fatigue, and an average of 20 minutes less sleep (Kashani et al, 2012).…”
Section: Stress Coping and Sleep Patternsmentioning
confidence: 99%
“…Sleep patterns have a significant impact on cardiovascular disease because of their connection to nocturnal dipping. Increased sleep disturbance limits the time spent asleep, resulting in higher nocturnal BPs and higher risk for cardiovascular disease later in life (Kashani et al, 2012).…”
Section: Stress Coping and Sleep Patternsmentioning
confidence: 99%